Types of Supplementary Aids and Services for Students With Significant Support Needs. (February 2019) - Kurth, Jennifer A.; Ruppar, Andrea L.; McQueston, Jessica A.; McCabe, Katie M.; Johnston, Russell; Toews, Samantha Gross
Supplementary aids and services (SAS) have been a provision in special education law since PL 94-142, however, almost no guidance has been provided to help teams make decisions about their appropriate selection and use. In this exploratory study, we explore the types of SAS selected for students with significant support needs using a conventional content analysis of individualized education program (IEPs) from 88 students in Grades K–12. Results illustrate the wide variation in types of SAS chosen for students overall. Curricular accommodations and personnel supports were the most commonly identified supports, while supports to assist students to communicate and make meaning of curriculum (e.g., curricular modifications) were less common, as were less intrusive supports such as peer-assisted learning. Implications for policy, practice, and research are provided.